Therapeutic Augmentation for Treatment-Resistant MDD - Sinclair, Heather Q. (MD Conference Express, 2009)
Major depressive disorder (MDD) affects about 15 million adults in the United States. Within that population, only one-third of patients who are treated with first-line antidepressant therapies achieve remission [Trivedi MH, Papakostas G, Perlis R. APA 2009]. Therefore, therapeutic augmentation, the addition of nonantidepressant compounds to an antidepressant regimen, may be a more reasonable option for those patients with first-line treatment resistance. This article explores the issue of treatment resistance in MDD and possible management strategies.